On the importance of being earnest about business: overcoming liberal arts students' misconceptions about leadership in corporate change processes - Ariane Berthoin Antal; Meinolf Dierkes (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Unfortunately, most students leave the university with little knowledge about decision-making in the public sector. Unless they study towards a management degree, most students experience little to no business education in their curricula. As a consequence, student perceptions of the business world are largely shaped by the fads and stereotypes propagated in ubiquitous business journals available in every airport bookstore worldwide. Since business plays an integral role in society, such unfamiliarity with business may have global social consequences. This article illustrates how a liberal arts class focusing on Europe's social and political integration employs a comprehensive case study about a corporate transformation process to provide students with insights into corporate leadership and strategic decision making. The article describes how, by reading and discussing the case study in conjunction with articles about organizational learning theory, students learn to effectively challenge the myths they hold about heroic leadership and the newest management fads. A key element in the course focuses on the role organizational politics plays in developing and implementing a new vision, a new organizational structure, and a new global strategy. – – Obwohl Unternehmen eine wichtige Rolle in der Gesellschaft spielen, werden Studenten außerhalb der Betriebswirtschaft noch zu selten an Fragestellungen aus dem Bereich der Unternehmenspolitik herangeführt. Wie strategische Entscheidungen in der Wirtschaft getroffen und umgesetzt und neue Visionen und Organisationsstrukturen entwickelt werden, sollte deshalb auch in das Lehrangebot für Geistes- und Sozialwissenschaftler aufgenommen werden. Dieser Artikel zeigt beispielhaft, wie Studenten, im Rahmen einer Lehrveranstaltung an einer US-amerikanischen Universität, anhand einer umfassenden Fallstudie über den Transformationsprozess des Pharmakonzerns Hoechst zum Global Player Aventis zur aktiven Auseinandersetzung mit Veränderungsprozessen in Unternehmen angeregt werden, die ganz anders sind, als die oft plakativen Managementlösungen, die die Business-Literatur dieser Tage zu bieten hat.
Keywords: 330; Betriebswirtschaftsstudium; Organisatorischer Wandel; Unternehmenspolitik; USA